Deteriogenic flora of the Phlegraean Fields Archaeological Park: ecological analysis and management guidelines. (18th May 2020) - Motti, Riccardo; Bonanomi, Giuliano; Stinca, Adriano
Abstract : Biodeterioration, the alteration caused by living organisms, on historical buildings and stone monuments is a well‐known problem affecting two‐thirds of the world's cultural heritage. The study of the flora growing on wall surface is of particular importance for the assessment of the risk of biodeterioration of stone artifacts by vascular plants, and for maintenance planning. In this study, we investigate how rock type, exposure and inclination of the wall affect the biodeteriogenic flora at 13 sites of the Archaeological Park of the Phlegraean Fields located in the province of Naples, in southern Italy. For each site, we analysed randomly selected square areas with 2 × 2 m size, representing the different vegetation types in terms of vascular plant species cover. The total number of plant species recorded was 129, belonging to 43 families. Erigeron sumatrensis, Sonchus tenerrimus and Parietaria judaica are the most commonly reported species, while Capparis orientalis is the species with the highest average coverage. Substrate type, exposure and surface inclination affect the floristic composition, with the average plant cover significantly higher on vertical surfaces and at western and southern exposure. All the main biodeteriogenic vascular plant species grow on more or less porous lythotype like yellow tufa, conglomerate and bricks. Finally, woody plants eradications methods are proposed by the tree cutting and local application of herbicides, to avoid stump and root sprouting and to minimize the dispersion of chemicals in the surrounding environment.